Pengembangan Ketrampilan dengan Pelatihan Memasak Aneka Hidangan Ikan Gurame kepada Kelompok Ekstra Kurikuler Tata Boga Siswa SMA Permai Pluit Jakarta - Yuliantoro, Nonot (Jurnal ABDIMAS PARIWISATA, 2020)
Cooking is an art to process raw materials into ready to eat dish with a proper cooking methods. To be able to cook well and properly people needs training at the right way. Pelita Harapan School of Hospitality and Tourism carry out community service cooking training activities aimed to the cooking club at Permai Senior High School Pluit Jakarta. The purpose of this community service is to share cooking skill and knowledge to the member of cooking club at Permai High School Pluit Jakarta since they need assistance to improve their cooking and food presentation skill. Pre test was conducted before the training to find out the basic skill and knowledge of cooking especially gurame fish, the ending of community service activities was carried out the post test to determine the effectiveness of the gurame cooking training that had been done. Cooking training activities to the member of cooking class Permai High School Students has a positive influence because the cooking club member became more skillfull and understand in processing gurame into various Nusantara Recipes.